Superfountain Effect Linked With 17 March 2015 Geomagnetic Storm Manifesting Distinct F3 Layer. Issue 7 (13th July 2019) - Venkatesh, K.; Patra, A.K.; Balan, N.; Fagundes, P.R.; Tulasi Ram, S.; Batista, I.S.; Reinisch, B.W.
Abstract: The existence of an additional stratification in the daytime equatorial ionospheric F region (the F 3 layer) was known since the 1940s. However, its characteristics and the underlying physical mechanism have been uncovered only recently. In this paper, we present and discuss the F 3 layer characteristics observed by six ionosondes distributed over equatorial and low latitudes (−20° to +25° dip latitudes) in the Brazilian longitude sector during the strongest geomagnetic storm (DstMin = −223 nT) of solar cycle 24, the St. Patrick's Day storm of 17 March 2015. Two eastward prompt penetration electric field (PPEF) events, as seen in equatorial electrojet, occurred during the main phase of the storm on 17 March 2015, a strong one (~100 nT) at around ~1200 UT and a weak one (~50 nT) at around ~1725 UT. Local time variations in the F 3 layer occurrence and ionospheric base height (h′F), peak height (hmF), and peak electron density (Nmax) are investigated. Notably, the F 3 layer occurred at all six locations, more distinctly during the stronger PPEF event. The large latitudinal extend in the occurrence of the F 3 layer in opposite hemispheres (−20° to +25° dip latitudes) covering the equatorial ionization anomaly crests observed for the first time is interpreted in terms of the combined effect of the super plasma fountain generated by the eastward PPEF and storm time equatorward neutral wind. Key Points: F 3 layer occurred over a large latitudinal extent from 20°S to 25°N dip latitudes during 17 March 2015 storm‐induced PPEF phases The PPEF‐generated superfountain led to the F 3 layer occurrence earlier at the equator and later at higher latitudes in both hemispheres F 3 layer was more distinct and stronger and lasted longer in the Northern Hemisphere due to the storm time asymmetric equatorward neutral winds